Association between PIK3CA Mutations in Blood and Tumor-Infiltrating Lymphocytes in Peruvian Breast Cancer Patients - Castaneda-Altamirano, CA (2022)
Objective: To evaluate the relationship between circulating tumor DNA (ctDNA) presence and tumor features including tumor-infiltrating lymphocyte (TIL) levels in Peruvian breast cancer patients. Materials and Methods: This was a prospective study conducted at the Instituto Nacional de Enfemedades Neoplasicas, Peru. We evaluated level of TIL and PIK3CA mutations in ctDNA. Clinical characteristics, including outcome data, were collected from the patient file. Survival was calculated from the date of blood sample drawn to the event time. Data collected were analyzed using SPSS software version 25. Results: We analyzed plasma samples from 183 breast cancer patients. most cases were of Luminal-B (44.8%) phenotype and stage II (41.5%), and median stromal TIL was 30%. PIK3CA mutation in ctDNA was detected in 35% cases (most with E545K) and was associated with lower TIL level (p=0.04). PIK3CA in ctDNA tended to be associated with advanced stages (p=0.09) in the whole series and with higher recurrence rates (p=0.053) in the non-metastatic setting. Patients with presence of PIK3CA in ctDNA tended to have shorter survival (p=0.083). Conclusion: Presence of PIK3CA mutation in ctDNA was frequently found in our Peruvian breast cancer series, was associated with lower TIL levels and tended to predict poor outcomes. © This work is licensed under a Creative Commons Attribution-Non Commercial 4.0 International License.